PENGARUH LATIHAN PLYOMETRIC TERHADAP KECEPATAN FOOTWORK BULUTANGKIS SISWA KELAS 11 MAN 3 MEDAN - Dinul Fitri Sinaga; Ilham Ari Affandi Purba; Ridho Albert Valentino Sinaga; Samuel Al Grindo Tampubolon; Mawardinur (STKIP Subang, 2026)
This study aims to determine the effect of plyometric training on the speed of badminton footwork among eleventh-grade students of MAN 3 Medan. Footwork speed is an important element in badminton because it supports players’ ability to move quickly and efficiently on the court. This study used an experimental method with a One Group Pretest-Posttest Design. The research sample was determined using a purposive sampling technique. The research instrument was a footwork speed test conducted before and after the plyometric training treatment. Data were analyzed using descriptive statistics and the t-test. The results of the study are expected to show that plyometric training has a significant effect on improving badminton footwork speed among eleventh-grade students of MAN 3 Medan. Therefore, plyometric training can be used as an effective training method to improve students’ footwork abilities.